S64 Rates and sites of recurrence following radical treatment of stage I lung cancer. (15th November 2016) - Kennedy, MPT; Lummis, KL; Spencer, K; Franks, K; Snee, M; Callister, MEJ
Abstract : Introduction: Lobectomy is the treatment of choice for medically operable patients with stage I lung cancer, with the best reported overall survival and lowest recurrence rates. Patient selection influences outcomes as demonstrated by wide variations in outcomes and reported recurrence rates for all radical lung cancer treatments. Some studies report recurrence rates following Stereotactic Ablative Radiotherapy (SABR) that are comparable to lobectomy. We aim to analyse the rates and site of recurrence in our patients who were radically treated for stage I lung cancer. Methods: All patients with two years follow-up after radical treatment for stage I lung cancer (2008–2013) were included. Retrospective review of electronic patient records to identify outcomes, including the presence and site of any recurrence. Results: 425 patients were identified. Treatment modalities included lobectomy 187 (44.0%), SABR 99 (23.3%), sub-lobar resection 85 (20.0%) and radical radiotherapy 54 (12.7%). There was pathological confirmation in 56.6% of SABR and 63.0% of radical radiotherapy. Patients treated with surgical resection were younger (mean age 69.0 vs 75.9 years, p < 0.001) and had a better performance status (PS0–1 83.5% vs 37.9%, p < 0.001), although larger tumours (T2a 53.4% vs 31.3%, p = 0.001). Mortality without cancer recurrence at two years was lower following surgery than non-surgical treatment (10.7% lobectomy and 11.8% sub-lobar resection vs 27.3% SABR and 25.9% radical radiotherapy, p < 0.001). Overall recurrence rates at two years were 12.3% lobectomy, 11.8% sub-lobar resection, 17.2% SABR and 29.6% radical radiotherapy – differences not significant on uni-variable regression, which may relate to small patient numbers. Figure 1 demonstrates the sites of recurrence. Considering only those with pathological confirmation of cancer, recurrence rates at two years were 17.9% for SABR and 32.4% for radical radiotherapy. Conclusions: The lowest recurrence rate was observed following surgical resection. In comparison, recurrence following SABR was non-significantly higher due to more loco-regional recurrence. Radical radiotherapy is associated with higher rates of overall, loco-regional and distant recurrence. Nodal recurrence was comparable between lobectomy, SABR and radical radiotherapy. This data is limited by low numbers as well as the confounding effects of early non-cancer deaths and incomplete pathological confirmation in the non-surgical treatment cohorts.